ANALISIS KESTABILAN LERENG PADA BATUAN LAPUK MENGGUNAKAN KRITERIA KERUNTUHAN GENERALIZED HOEK-BROWN DAN MOHR-COULOMB EKUIVALEN - Hery Mulyanto (Direktorat Bina Teknik Jalan dan Jembatan, 2022)
In the soil failure model, the strength of soil masses is controlled by the friction of grains, as analogous to the strength of intact rock in the rock mass failure. Discontinuity strength is obviously not considered in the soil failure criterion. Slopes of weathered rock masses analyzed in this paper were located on the two cut slopes of highway construction on the southern coast of East Java, Serang Beach – Malang Regency Section. The rock mechanic approach was applied by using a non-linear failure criterion of generalized Hoek-Brown. This criterion was correlated to the linear failure criterion of Mohr-Coulomb which was common in a slope stability analysis practice. Analysis using generalized Hoek-Brown was always generating critical factor of safety (FS), compared to the Mohr-Coulomb equivalent with FS difference of 50.5% and 16.03% at the STA. 16+350 and STA. +14+125 respectively. Critical slip surfaces produced by generalized Hoek-Brown were always laying on the shallower area, compared to the Mohr-Coulomb critical slip surfaces. Keywords: weathered rock slope, generalized hoek-brown, equivalent mohr-coulomb, geological strength index, southern coast java road.